Regina Dauser, Stefan Hächler, Michael Kempe, Franz Mauelshagen, Martin Stuber (eds.), Wissen im Netz. Botanik und Pflanzentransfer in europäischen Korrespondenznetzen des 18. Jahrhunderts (Altre Modernità, 2013)
(Berlin, Akademie Verlag, 2008, 427 pp. ISBN 978-3-05-004144-5)di Elena Canadelli